Evaluación de la bioacumulación de (as) y (cd), en cultivos de lactuca sativa y daucus carota, en suelos agrícolas de la parroquia Toacaso, provincia de Cotopaxi, período 2019-2020. - Alvarez Agama, Carla Estefania (2020)
The research was carried out in order to evaluate the bioaccumulation of (As) and (Cd) in crops of Lactuca sativa and Daucus carota, in agricultural soils of the Toacaso Parish; by the determination of concentrations of these heavy metals in both soil and crops and then comparing the results obtained with the TULSMA Annex 2 Regulation for soil, the INEN-CODEX 193 Regulation and the MERCOSUR Technical Regulation for food. Sampling carried out for soil in Zig-Zag, from which a composite sample was obtained in both initial soil and cultivated soil, which took at a depth of 30 cm; for crops, simple random sampling carried out in an area of 14 m2. Also, three samples of Lactuca sativa and nine samples of Daucus carota were taken. The results obtained in the laboratory determined that (As) for soil sampling showed concentrations of 40,031 mg/kg and 51,651 mg/kg, which did not meet the maximum allowable limits; (Cd) the two samples showed concentrations of <0,50 mg/kg, complying with the maximum permissible limits. For the Lactuca sativa culture, the concentration of 0.143 mg/kg for (As) and the concentration for (Cd) of <0.050 mg/kg were determined, complying with the two concentrations with the stipulated maximum limits. For the cultivation of Daucus carota, the concentration of 0.349 mg/kg for (As), which does not meet the stipulated maximum limit, was determined; the concentration of (Cd), presented a value of 0.059 mg/kg, complying with the stipulated maximum limit. Finally, it generated a new remediation alternative for agricultural soils contaminated by heavy metals, the use of other accumulating species such as large onion Allium fistulosum, and Beta Vulgaris var chard ciola.